Mesomorphism and electrochemistry of thienoviologen liquid crystals1. Issue 27 (21st July 2015) - Cospito, S.; Beneduci, A.; Veltri, L.; Salamonczyk, M.; Chidichimo, G.
<x xml:space="preserve">Abstract</x> New π-conjugated ionic liquid crystals with a strong electron-acceptor thienoviologen core are potentially exploitable as electroactive materials in organic electronics.